Utilization of Chicken Meat in terms of Physical and Chemical Contamination - Febrianta, Harvey (SEEIJ (Social Economics and Ecology International Journal), 2022)
Chicken meat products in the presentation process need to pay attention to quality and safety. The nutritional content of broiler chicken meat is quite high when it is stored for more than 2 days it will be easily damaged. This study aims to determine the utilization of ginger by curing method on broiler chicken meat. The research treatments were as follows: T0: Control chicken meat, T1: Chicken meat with the addition of 1% ginger powder, T2: Chicken meat with the addition of 2% ginger powder, T3: Chicken meat with the addition of 3% ginger powder. The scores given are: (1) do not like; (2) rather like; (3) likes; and (4) really like it. Assessment based on a score of 1 - 4 was given by the panelists on the questionnaire that had been provided. The panelists who were asked to carry out the organoleptic assessment were panelists with slightly trained criteria of 8 people. Before carrying out the organoleptic assessment, the panelists were introduced to the material (sample) to be tested by practicing organoleptic testing. The results showed that the T3 treatment was the best treatment in the sensory tests conducted. Based on sensory data regarding the use of chicken meat that is free from physical and chemical contamination, it can be concluded that the quality of chicken meat can be improved in several ways, one of which is by adding ginger so that sensory quality increases. Ginger is proven to be able to reduce the fishy smell of chicken meat and its bioactive components can prevent physical and chemical damage to chicken meat.